Metamagnetism in nanosheets of Co-II-MOF with T-N at 26 K and a giant hysteretic effect at 5 K - Gupta, Kriti; Dadwal, Arun; Rana, Shammi; Jha, Plawan Kumar; Jain, Anil; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Inorganic Chemistry, 2018)
Herein, we have synthesized at room-temperature two-dimensional nanosheets of a MOF comprised of cobalt(II) ion with benzenedicarboxylic acid ligand, which exhibited unusual magnetic properties. Direct-current magnetic susceptibility revealed an anti-ferromagnetic (AFM) transition at 26 K (Neel temperature, T-N) followed by a canting of the spin moments along with the concomitant appearance of a sigmoidal-shaped magnetization versus field (M-H) curve at 15 K. Such a canted AFM ordering led to nonzero remnant magnetization with a remarkably high coercive field of similar to 10 kOe at 5 K. Metamagnetism was further: substantiated by the alternating-current magnetic susceptibility measurements.